The impact of pimavanserin on psychotic phenotypes and tau phosphorylation in the P301L/COMT– and rTg(P301L)4510 mouse models of Alzheimer's disease - Heidy Jimenez; Leslie Adrien; Adam Wolin; John Eun; Eric H. Chang; Ethan S. Burstein; Jesus Gomar; Peter Davies; Jeremy Koppel (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Psychosis in Alzheimer's disease (AD) is associated with grave clinical consequences including a precipitous cognitive decline and a hastened demise. These outcomes are aggravated by use of existing antipsychotic medications, which are also associated with cognitive decline and increased mortality; preclinical models that would develop new therapeutic approaches are desperately needed. The current report evaluates the ability of the neoteric antipsychotic, pimavanserin, to normalize hyperkinesis and sensorimotor gating in the novel catechol‐O‐methyltransferase (COMT) deleted P301L/COMT– and rTg(P301L)4510 models of psychotic AD, and the impact of pimavanserin on tau pathology. Methods Female P301L/COMT– mice were behaviorally characterized for abnormalities of locomotion and sensorimotor gating, and biochemically characterized for patterns of tau phosphorylation relative to relevant controls utilizing high‐sensitivity tau enzyme‐linked immunosorbent assay (ELISA). Female P301L/COMT– and rTg(P301L)4510 mice were randomized to pimavanserin or vehicle treatment to study the ability of pimavanserin to normalize locomotion and rescue sensorimotor gating. Additionally, high‐sensitivity tau ELISA was used to investigate the impact of treatment on tau phosphorylation. Results P301L/COMT– mice evidenced a hyperlocomotive phenotype and deficits of sensorimotor gating relative to wild‐type mice on the same background, and increased tau phosphorylation relative to COMT‐competent P301L mice. Pimavanserin normalized the hyperkinetic phenotype in both the P301L/COMT– and rTg(P301L)4510 mice but had no impact on sensorimotor gating in either model. Pimavanserin treatment had little impact on tau phosphorylation patterns. Discussion These data suggest that pimavanserin ameliorates tau‐driven excessive locomotion. Given the morbidity associated with aberrant motor behaviors such as pacing in AD and lack of effective treatments, future studies of the impact of pimavanserin on actigraphy in patients with this syndrome may be warranted.